2004
DOI: 10.1103/physrevlett.92.201305
|View full text |Cite
|
Sign up to set email alerts
|

Regularization of the Linearized Gravitational Self-Force for Branes

Abstract: We discuss the linearized, gravitational self-interaction of a brane of arbitrary codimension in a spacetime of arbitrary dimension. We find that in the codimension two case the gravitational self-force is exactly zero for a Nambu-Goto equation of state, generalizing a previous result for a string in four dimensions. For the case of a 3-brane, this picks out the case of a six-dimensional brane-world model as having special properties which we discuss. In particular, we see that bare tension on the brane has no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
(30 reference statements)
0
20
1
Order By: Relevance
“…In [16] it was shown that the regularized gradient operator applies more generally, and this was used in the case of purely gravitational fields in [17]. The cancellation of the gravitational self-force, already known for the case of a Nambu-Goto string in four spacetime dimensions, was seen to hold for any Nambu-Goto brane of co-dimension two, whatever the spacetime dimension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [16] it was shown that the regularized gradient operator applies more generally, and this was used in the case of purely gravitational fields in [17]. The cancellation of the gravitational self-force, already known for the case of a Nambu-Goto string in four spacetime dimensions, was seen to hold for any Nambu-Goto brane of co-dimension two, whatever the spacetime dimension.…”
Section: Introductionmentioning
confidence: 99%
“…We can deal with all these cases, leaving aside only the hypersurface case of codimension one, by introducing a regularization factor [16,17] of the form…”
Section: Allowance For Regularized Self Interactionmentioning
confidence: 99%
“…[32], the last term in (79) is a problem when we consider localizing gravity on the brane. To see why, we consider the Einstein equations (20), (21) and (22) for our metric (1). In the asymptotic limit r → ∞, we require a solution to the Einstein equations that is Anti-de-Sitter, that is we require R ∼ const.…”
Section: Discussionmentioning
confidence: 99%
“…But it follows from expressions (66) and (69) that the overall coefficient of this divergence is equal to zero. In the linearized gravity approximation, this fact was established in [12]. Therefore, the gravitational self-coupling of a codimension-two brane (and also of a hyperbrane) is not only renormalizable but also finite in all orders of the perturbation theory.…”
Section: Self-coupling In Nonlinear Theoriesmentioning
confidence: 91%
“…The effective equations of motion for a point charge in a curved background space-time [3], for a spinning particle [4], for a massive particle in higher dimensions [5], [6], for a massless charged particle in d = 4 [7], and for a massive particle coupled to the linearized gravity background [8] are currently known. Advances in string theory have motivated the study of the radiation back-reaction problem in models of extended relativistic objects (branes) [9]- [12]. Despite a variety of models, all these works share the common point that the fields considered satisfy linear equations of motion with a singular source (current) in the right-hand side.…”
Section: Introductionmentioning
confidence: 99%